Le sida, risque assurable - Millette, Yves (Assurances, 1988)
Our collaborator, Mr. Millette, focuses his article on statistics, which form the very basis of the major principles of insurance: the sharing and the evaluation of risks. He looks at the question of screening and medical questionnaires and at the high rates charged by insurers in the hope that a better understanding of mortality and morbidity statistics specifically related to AIDS will help to eventually solve this problem.